2022
DOI: 10.1007/s00484-022-02370-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the impact of heat on human physical work capacity; part IV: interactions between work duration and heat stress severity

Abstract: High workplace temperatures negatively impact physical work capacity (PWC). Although PWC loss models with heat based on 1-h exposures are available, it is unclear if further adjustments are required to accommodate repeated work/rest cycles over the course of a full work shift. Therefore, we examined the impact of heat stress exposure on human PWC during a simulated work shift consisting of six 1-h work-rest cycles. Nine healthy males completed six 50-min work bouts, separated by 10-min rest intervals and an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 43 publications
0
10
0
1
Order By: Relevance
“…Fifty‐six sources were retained for full‐text screening, to which 28 sources were added from cross‐referencing. In the end, 49 sources met the inclusion criteria, of which 35 (71%) were original studies 16,26–28,35–37,39–66 and 14 other sources: five technical reports, 14,67–70 three reviews, 71–73 two guidelines, 21,22 two book chapters, 74,75 one symposium paper, 76 and one abstract 77 . No Cochrane review, systematic review, nor meta‐analysis was found.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fifty‐six sources were retained for full‐text screening, to which 28 sources were added from cross‐referencing. In the end, 49 sources met the inclusion criteria, of which 35 (71%) were original studies 16,26–28,35–37,39–66 and 14 other sources: five technical reports, 14,67–70 three reviews, 71–73 two guidelines, 21,22 two book chapters, 74,75 one symposium paper, 76 and one abstract 77 . No Cochrane review, systematic review, nor meta‐analysis was found.…”
Section: Resultsmentioning
confidence: 99%
“…No laboratory study focused on the combination of physical and mental tasks performed concurrently. Of the 33 experimental studies that investigated endurance tasks or a combination of endurance and mental tasks, 25 (76%) used a single‐task such as walking, 35,37,40,43,45,47,49,50,52,59–61,63–65 cycling, 26–28,39,42,51,62,66 or block stepping 44,48 . The remaining eight studies (24%) incorporated specific occupational tasks related to agriculture, construction, and tourism, 16 welding, 36 repetitive box lifting, 54 walking with load carrying, 49,55,56 walking with arm curls, 58 or walking with shoveling 53 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations